2004
DOI: 10.1103/physrevlett.92.115507
|View full text |Cite
|
Sign up to set email alerts
|

Size- and Temperature-Dependent Structural Transitions in Gold Nanoparticles

Abstract: Size- and temperature-dependent structural transitions in gold nanoparticles were revealed with morphology statistics obtained by high-resolution electron microscopic observations for thousands of particles annealed in a helium heat bath. We found that gold nanoparticles over a wide size range, 3-14 nm, undergo a structural transformation from icosahedral to decahedral morphology just below the melting points. It was also clarified that the formation of bulk crystalline structures from the decahedral morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
234
3
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(255 citation statements)
references
References 27 publications
16
234
3
2
Order By: Relevance
“…Our results imply that transitions to a stable crystalline phase do not occur easily because of the energy barriers. Our results agreed with those of previous studies, suggesting that several kinds of clusters can coexist in the same size range, such that structural transitions are not sharp [19,20]. If the clusters grow further, the third step of nucleation occurs to form stable clusters, although we did not observe this in our simulations.…”
Section: E Crystalline Structures Of Clusterssupporting
confidence: 67%
See 1 more Smart Citation
“…Our results imply that transitions to a stable crystalline phase do not occur easily because of the energy barriers. Our results agreed with those of previous studies, suggesting that several kinds of clusters can coexist in the same size range, such that structural transitions are not sharp [19,20]. If the clusters grow further, the third step of nucleation occurs to form stable clusters, although we did not observe this in our simulations.…”
Section: E Crystalline Structures Of Clusterssupporting
confidence: 67%
“…The structure of nanocrystal clusters is also important in scientific and technological applications [6][7][8][9]. It is known that the structure of an atomic cluster is a function of material component and temperature as well as the number of atoms in the cluster [9][10][11][12][13][14][15][16][17][18][19][20][21]. Many theoretical calculations and experiments have been conducted on size-dependent structures in atomic clusters for various materials, and they have shown that structures for nanoclusters have a variety of characteristics [9,11,15,[18][19][20]22].…”
Section: Introductionmentioning
confidence: 99%
“…For such calculations, we used the thermodynamic parameters of the bulk metals. Finitesize effects in elemental metal NPs can induce changes in the structural, vibrational and thermodynamic properties relative to bulk material including differences in bond length [20][21][22][23], Einstein temperature [23,24] and melting temperature [25]. However, these effects are typically significant only for NPs of diameter considerably less than those used in this report and, as a consequence, any error introduced through our use of bulk values was considered minimal.…”
mentioning
confidence: 90%
“…Gold nanoparticles over a wide size range, 3-14 nm, undergo a structural transformation from icosahedral to decahedral morphology just below the melting points. [7] The various preparations of the monometallic systems Au/SiO 2 , Au/MgO and Au/Al 2 O 3 , have demonstrated that it is difficult to obtain small monodisperse gold particles. [8 -10] The particles obtained have an average diameter between 3 and 200 nm depending on the method of preparation.…”
Section: Introductionmentioning
confidence: 99%